A note on the application of the vortex tube to ventilated suits - Westley, R. (College of Aeronautics, 1953)
The vortex tube has no moving parts and its makes it an attractive form of refrigerator when a source of compressed air is available. The drawback is that this device has a low efficiency. The proposed application involves passing compressed air, from a jet engine, through a precooler and a vortex tube to the ventilated suit. Investigations show that the temperature of the air entering the ventilated suit is decreased as engine compression ratio and precooler efficiency are increased. Increase of the aircraft's forward speed will result in decreased cooling until a maxim= Mach number is reached above which the ventilated suit cooling requirement, of 115o F, can no longer be satisfied. The maximum permissible Mach number, for an aircraft flying at sea level under the maximum ambient tropical temperature of 45°C, has been calculated over a range of compression ratios, 3 - 15 and precooler efficiencies, 75 - 100 per cent. These results are plotted in figures 6 and 7. It is found that a practical application requires a precooler efficiency of not less than. 80. per cent.